Mullerian adenosarcoma accidentally detected and coexisting with cervical carcinoma in situ: a rare case report - Qing, Xuemei; Xie, Min; Guo, Hongying; Zhang, Liying; Ye, Jiatian; Zhang, Yong; Ma, Ying (Frontiers in Oncology, 2024)
Mullerian adenosarcoma is rare, usually found in the uterine corpus and rarely in the cervix. Adenosarcoma that grows diffusely in the uterine cavity and the cervical canal is even rarer without symptoms. Herein, we report a rare case of multiple primary malignant neoplasms of Mullerian adenosarcoma accidentally detected and coexisting with cervical carcinoma in situ. Fortunately, the tumor was in the early stage and the Mullerian adenosarcoma was treated together with the cervical carcinoma in situ by hysterectomy + bilateral adnexectomy. Histopathology and immunohistochemistry results confirmed this diagnosis, further confirmed by a pathology consultation at the University Hospital. The patient recovered well from the surgical treatment and was discharged with regular follow-up. The patient did not undergo pelvis–abdomen CT and diagnostic curettage preoperatively, and no malignancy was detected by cryo-pathology intraoperatively, which may be related to the rarity of the disease and the relative lack of awareness and experience of our clinicians and pathologists for this tumor. We hope that this rare case can provide some lessons for gynecologists and pathologists.